1975
DOI: 10.1161/01.res.37.5.534
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of sequential stimuli applied during the relative refractory period in relation to determination of fibrillation threshold in the canine ventricle.

Abstract: An ineffective stimulus applied to cardiac tissue within the relative refractory period can alter the response to an immediately subsequent stimulus. We observed three response patterns that can coexist at different sites of stimulation in the same heart. In the first pattern, a stimulus of two to ten times diastolic threshold, applied too early to elicit a propagated response, becomes effective when a stimulus of equal strength is delivered 10 msec earlier. In the second pattern, a stimulus applied just late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…Studies on anaesthetized dogs demonstrate that RV stimulations are associated with lower VF threshold and higher inducibility of arrhythmia upon ectopic activation, compared to the spatially matched (either epicardial or endocardial) LV stimulations . In human patients with a documented history of spontaneous arrhythmia, a sustained ventricular tachycardia is more often inducible by programmed electrical stimulation applied to the RV compared to the LV endocardium .…”
Section: Impact Of Ventricular Pacing Site On Arrhythmic Vulnerabilitymentioning
confidence: 99%
“…Studies on anaesthetized dogs demonstrate that RV stimulations are associated with lower VF threshold and higher inducibility of arrhythmia upon ectopic activation, compared to the spatially matched (either epicardial or endocardial) LV stimulations . In human patients with a documented history of spontaneous arrhythmia, a sustained ventricular tachycardia is more often inducible by programmed electrical stimulation applied to the RV compared to the LV endocardium .…”
Section: Impact Of Ventricular Pacing Site On Arrhythmic Vulnerabilitymentioning
confidence: 99%
“…However, there are certain drawbacks to this technique which have recently been investigated. 8 ' 15 One of the problems associated with using trains of stimuli is that anodal stimuli placed in the absolute refractory period can shorten its duration and cathodal stimuli can lengthen it. 8 This would heighten the disparity of cathodal and anodal refractory periods and hence the use of trains of stimuli may not be a desirable method for the comparison of the ability of cathodal and anodal stimuli to evoke fibrillation.…”
Section: Harris and Moe In 1942mentioning
confidence: 99%
“…Lewis and Drury2 made similar observations in the dog atrium. Tamargo et al 3 demonstrated that subthreshold stimuli could inhibit threshold stimuli from activating canine ventricle.…”
mentioning
confidence: 99%